Storage of Vital Archives of Land Acquisition: Case Study in Public Company (Perum) Jasa Tirta I - Edwin, U'ung; Setiawan; edwin, uung (Jurnal Tadwin, 2025)
Vital archives are important documents that support company operations, especially in the land acquisition process related to legality and land ownership. However, the storage of these archives is still not up to standard, making access difficult and increasing the risk of information loss. This study aims to examine the process of storing vital archives for land acquisition at Perum Jasa Tirta I, identify the obstacles faced, and provide suggestions for improvement. The method used is a qualitative approach with observation, interview, and documentation techniques. The research informants came from the Legal and Archives Subdivision which plays a direct role in archive management. The results of the study show that archive storage is still manual and does not comply with archival standards. The main obstacles faced are the absence of special SOPs, limited competent human resources, and lack of storage facilities. Optimization is needed through the preparation of guidelines, improving infrastructure, and training for archive officers to support the efficiency, security, and sustainability of vital archive information